(untitled) (Heritage, 2025)
In the conditions of modern security of the 21st century, talking about the concept of terrorism means talking about one of the main terms in the political vocabulary. The permanent application of modern scientific and technological achievements contributes to the development of new forms and forms of terrorist activity, which indicates that terrorism is not only political, but also a legal, historical, security, sociological, psychological and media phenomenon. Therefore, a multidisciplinary approach is required for scientific and professional study. Globalization, as a process of cultural, political, and economic connection, is present in almost all segments of society, and in support of that, it is inevitable to point out that terrorism today has a global character and is a global security threat. In parallel with the development of civil air traffic, the number of terrorist attacks has increased. Hijacking, planting explosive devices on aircraft, various forms of sabotage, collisions of aircraft on the ground and in the airspace, are just some of the types of terrorist attacks, while the vulnerability of civilian air traffic to terrorism has become increasingly certain.